Clinical efficacy of dalbavancin for the treatment of acute bacterial skin and skin structure infections (ABSSSI) - Leuthner, Kimberly D (Ther Clin Risk Manag, 2016)
Acute bacterial skin and skin structure infections (ABSSSI) are a common disease causing patients to seek treatment through the health care system. With the continued increase of drug-resistant bacterial pathogens, these infections are becoming more difficult to successfully cure. Lipoglycopeptides have unique properties that allow the drug to remain active toward both common and challenging pathogens at the infected site for lengthy periods of time. Dalbavancin, a new lipoglycopeptide, provides two unique dosing regimens for the treatment of ABSSSI. The original regimen of 1,000 mg intravenous infusion followed by a 500 mg intravenous infusion after a week has been shown as safe and effective in multiple, randomized noninferiority trials. These studies also demonstrated that dalbavancin was similar to standard regimens in terms of both safety and tolerability. Recently a single 1,500 mg dose was demonstrated to be equivalent to the dalbavancin two-dose regimen for treating ABSSSI. With the introduction of dalbavancin, clinicians have the option to provide an intravenous antimicrobial agent shown to be as effective as traditional therapies, without requiring admission into the hospitals or prescribing a medication which may not be utilized optimally. Further understanding of dalbavancin and its unusual properties can provide unique treatment situations with potential benefits for both the patient and the overall health care system, which should be further explored.